Internacionalização das instituições de ensino superior: impactos no corpo técnico-administrativo da Universidade Federal do Rio de Janeiro - Souza, Izabel Cristina Dias de (2015)
The internationalization of higher education is being conducted as a way to improve higher education, and this, as a transmitter of new knowledge. From what we propose on the research problem, the choice of the Federal University of Rio de Janeiro (UFRJ) is justified by the fact that it is an institution that is in the process of institutionalizing their internationalization actions. The study of the theme became important due to the new demands which the internationalization process faces. This increasing demand has raised the increase of requirements of highly qualified professionals to develop their professional activities in the international relations sectors (IR) of UFRJ. Therefore, the objective of the study was to investigate how the internationalization process of UFRJ impacts the training and qualification programs for administrative staff in education (ASE) of UFRJ who work exclusively in the International Affairs Office at the Rector’s Office (SCRI), in the Academic Division of International Relations of Polytechnic School (DARI / POLI) and the International Relations Section at the Faculty of Architecture and Urbanism / FAU. It was considered as a time frame the period between 2008 and 2013. To achieve the goal, it was made a single case study, with a qualitative and explanatory approach. Initially, it was made an extensive bibliographic research. Then, information was collected through documentary research. After that, questionnaires were applied to the ASE from the three sectors involved in the study and semi structured interviews were made for the target group which is made of managers professors and managers of Administrative Staff. The analysis of these data was made through the analysis of content and through the triangulation between data sources and theoretical foundation. The results allowed us to evaluate the impact of this process regarding the professional activities of ASE and the policies of programs of professional development of UFRJ. We concluded that the internationalization of the university has a negative impact for the ASE who work in sector of International Relations and that the institution in question does not have professional development program directed to these workers.